Allergic Rhinitis during Pregnancy -an Update of Management (Medicine Today, 2017)
The concurrence of allergic rhinitis and pregnancy is common. The diagnosis of allergic rhinitis is easily and reliably made, by eliciting the characteristic symptoms on history. This diagnosis is easily confirmed by using the radioallergosorbent test (RAST) or enzyme-linked immunosorbent assay(ELISA) tests. Nasal symptoms, particularly obstruction, are often aggravated in pregnancy, through several possible mechanisms. The disease is often pre-existing and sometimes coincidental during pregnancy, and can worsen, improve, or stay the same during pregnancy. Besides ameliorating the detrimental effects of AR on the patient's quality of life, correct treatment is important for controlling concomitant asthma. If possible, it is important to highlight the risks of not taking such medications at a pre-conception visit. Although most medications for AR readily cross the placenta, there are several choices of treatment for controlling the symptoms during pregnancy. The choices may be varied depending on the disease course and symptoms, and inhaled corticosteroids are considered to be the first-line medical treatment. In addition, either a first-generation antihistamine, such as chlorpheniramine, or a secondgeneration antihistamine, such as cetirizine or loratadine, can be prescribed as the second-line medical treatment. As an alternative, intranasal cromolyn can be prescribed safely. Some of the leukotriene receptor antagonists and nasal decongestant sprays can only be prescribed when other methods are no longer valid and strict benefits can be expected. It is considered safe to continue immunotherapy during pregnancy.Medicine Today 2016 Vol.28(2): 83-88